Investigation on the electronic and physical properties of gamma-MnS films as a function of thickness. (15th March 2022) - Ulutas, C.; Erken, O.; Gunes, M.; Ozkendir, O.M.; Gumus, C.
Abstract: In this study, gamma-manganese sulphide (γ-MnS) films were prepared at various thickness and deposition time at a temperature of 50 °C by Chemical Bath Deposition Method (CBD). The characterization of the gamma-MnS films were determined by using the following methods; X-ray Absorption Fine Structure Spectroscopy (XAFS), X-ray diffraction (XRD), optical absorption, Field Emission-Scanning Electron Microscope (FE-SEM), Energy Dispersive X-ray analysis (EDX). The electronic interplay via the coupling between Mn 3 d levels and S 2 p levels was determined to build up strong molecular bonds containing broad band with hybrid pd levels at low energy levels. The results of the electronic structure analysis were also tested with the absorption spectroscopy calculations and high agreement is reported. XRD analysis revealed that the film deposited for 5 h had amorphous structure and turned to be crystal structure in hexagonal phase with deposition time 10, 15, 20 h due to increasing film thickness value. The optical band gap values were reduced from 3.86 eV to 3.10 eV with increasing film thickness. The average refractive index value of films at visible region were calculated between 1.55 and 2.81 as a function of increment in film thickness. The mobility and resistivity of the films were measured as 8.65–55.76 cm 2 /Vs and 3.10 × 10 5 –2.39 × 10 6 Ωcm, respectively, by Hall measurement. Highlights: The electronic interplay via the coupling between Mn 3 d levels and S 2 p levels was determined to build up strong molecular bonds containing broad band with hybrid pd levels at low energy levels. The effect of various thickness on the physical and electronic properties of gamma-MnS thin films was investigated. The best crystallization of gamma-MnS thin films is occurred in the film with a thickness of 2.50  μ m, which was deposited for 5 h. The optical energy band gap decreased by increasing the thickness of gamma-MnS films. The mobility and resistivity of the films were measured as 8.65–55.76 cm 2 /Vs and 3.10 × 10 5 –2.39 × 10 6 Ωcm, respectively.